The Effect Of Burnout, Workload And Perceived Organizational Politic On Turnover Intention For Coal And Mineral Company Employees In Indonesia - Annisa Ayu Budhiarti; Setyo Riyanto (Journal Research of Social Science, Economics, and Management, 2022)
The mobility of talented and highly skilled employees is an important issue for organizations. Job satisfaction, commitment, equality, and many other factors have been identified as explanations. Changes in organizational settings; however, no agreed standard framework is superior. When an organization is going through some kind of change process. In today's rapidly changing environment, change has become an ongoing process for organizations to respond to changing environmental factors such as technology, global demand and economic cycleThis study aims to analyze the effect of workload, burnout, and perceived organizational politics on the effect of turnover intention. This study's population is employees working in Indonesia's coal and mineral mining industry. With a sample of 150 workers. The data method uses Multiple Linear Regression. The results of this study found that workload did not have a significant impact on turnover intention. Burnout has an impact on increasing employee turnover intention. Perceived organizational politics is also able to encourage turnover intention. The implications of this research are discussed in the article